TUTURAN DIREKTIF FILM UMAR BIN KHATTAB EPISODE 1-15 (TINJAUAN PRAGMATIK) (Universitas Negeri Semarang, 2022)
Directive speech acts are speech acts that function to direct the speech partner to do something. The purpose of this study is to increase understanding of the directive speech acts contained in the film Umar Bin Khattab. This research is a qualitative research with a descriptive qualitative research design. The data is in the form of directive speech acts with the data source of the Umar Bin Khattab film. The instrument used in this research is a data card. The data collection technique used the referencing method. The data collection technique used the equivalent method. The results of this study indicate that in the film Umar Bin Khattab found 104 data, with the following divisions: 21 utterances in the form of requests, 39 utterances in the form of questions, 22 utterances in the form of orders, nine utterances in the form of prohibitions, five utterances in the form of giving permission, and eight utterances in the form of advice. . Of the six types of directive speech acts in this film, the question form is the most used, and the permission form is the least used.